The Influence of Work Climate, Job Satisfaction, and Loyalty on Teacher Performance in Muhammadiyah Elementary Schools in Bandung City - Saphira , Adinda Nur; Muhammad Zuhaery; Ika Maryani (Universitas Ahmad Dahlan, 2025)
This study aims to describe the conditions in Muhammadiyah Elementary Schools throughout Bandung City with a focus on work climate, job satisfaction, teacher loyalty, and teacher performance. In addition, this study also analyzes the influence of these three factors on teacher performance, which includes teaching quality and involvement in school activities, and their impact on students. This study uses a quantitative approach involving 144 teachers from various Muhammadiyah Elementary Schools in Bandung City. The results of the analysis show that work climate has a significant effect on teacher performance (significance value 0.000), with a positive work atmosphere, such as harmonious relationships and adequate facilities, proven to improve teacher performance, although there is still room for improvement in aspects of communication and environmental cleanliness. Then, job satisfaction also has a significant effect on teacher performance (significance value 0.023), where teachers who are satisfied with their salary, work environment, and management support show better performance, although aspects of incentives and relationships with superiors still need to be improved. In addition, teacher loyalty also has a significant effect on teacher performance (significance value 0.023), where teachers who have high loyalty tend to show optimal performance, which can be driven by a supportive work environment and positive relationships with management. Overall, improving the work climate, job satisfaction, and teacher loyalty not only improves teacher performance but also contributes to the quality of education and student development in Muhammadiyah Elementary Schools throughout Bandung City.